2022
DOI: 10.1002/jsfa.12307
|View full text |Cite
|
Sign up to set email alerts
|

Treatments of heating and ultrasound improve the inhibition of gallocatechin gallate on tyrosinase

Abstract: BACKGROUND: Gallocatechin gallate (GCG), a catechin of tea polyphenols, possesses inhibitory ability against tyrosinase, but few studies have reported how common processing methods affect it. In this research, the influence of heating and ultrasound treatments on the inhibition of GCG against tyrosinase was explored by ultraviolet-visible absorption, fluorescence spectroscopy, high-performance liquid chromatography and liquid chromatography-tandem mass spectrometry.RESULTS: Both heating and ultrasound treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Hong et al reported that both heating and ultrasound treatments of GCG alone improved GCG's inhibitory ability against tyrosinase compared with the untreated. The enhanced inhibition of treated GCG on tyrosinase may be due to partial conversion of GCG into EGCG and GA 22 .…”
Section: Enzyme Inhibitory Activitymentioning
confidence: 99%
“…Hong et al reported that both heating and ultrasound treatments of GCG alone improved GCG's inhibitory ability against tyrosinase compared with the untreated. The enhanced inhibition of treated GCG on tyrosinase may be due to partial conversion of GCG into EGCG and GA 22 .…”
Section: Enzyme Inhibitory Activitymentioning
confidence: 99%